Regret following female sterilization in Slovenia. Issue 1 (July 2015) - Becner, Anja; Turkanović, Anela Bečić; But, Igor
Abstract: Objective: To estimate the regret rate and risk factors for regret among women who have undergone sterilization. Methods: A retrospective study was conducted among all women who underwent a sterilization procedure at the University Medical Center Maribor, Maribor, Slovenia, in 2008–2012. Identified women were contacted and asked to complete an online questionnaire assessing regret and symptoms associated with depression. Results: Among 714 identified women, 308 (43.1%) completed the questionnaire. Four (1.3%) participants reported regret, and 9 (2.9%) reported that they would not opt for sterilization again, all of whom had post-sterilization problems. Such problems were significantly associated with participants reporting that they would not opt for sterilization again ( P  = 0.003). Additionally, women who would not choose sterilization again had significantly higher scores on the depressive scale used than did those who would undergo sterilization again ( P  = 0.028). Conclusion: Few women report regret after tubal sterilization in Slovenia. However, an additional consultation on post-sterilization problems and depressive disorder before sterilization might minimize the risk of regret.